2010
DOI: 10.1523/jneurosci.2565-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Punishing an Error Improves Learning: The Influence of Punishment Magnitude on Error-Related Neural Activity and Subsequent Learning

Abstract: Punishing an error to shape subsequent performance is a major tenet of individual and societal level behavioral interventions. Recent work examining error-related neural activity has identified that the magnitude of activity in the posterior medial frontal cortex (pMFC) is predictive of learning from an error, whereby greater activity in this region predicts adaptive changes in future cognitive performance. It remains unclear how punishment influences error-related neural mechanisms to effect behavior change, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 42 publications
5
35
1
1
Order By: Relevance
“…In addition, participants showed faster reaction times after trials that did not provide positive social reinforcement. This finding is similar to studies that demonstrate improved performance on a trial that follows receiving punishment (Hester et al, 2010) or choosing to make a bet more often after losing money than winning money (Liu et al, 2007), though the present study did not assess strategic behavior directly. Taken together, the behavioral findings demonstrate that participants learned the reinforcement contingencies and thus provide an objective index of social learning.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, participants showed faster reaction times after trials that did not provide positive social reinforcement. This finding is similar to studies that demonstrate improved performance on a trial that follows receiving punishment (Hester et al, 2010) or choosing to make a bet more often after losing money than winning money (Liu et al, 2007), though the present study did not assess strategic behavior directly. Taken together, the behavioral findings demonstrate that participants learned the reinforcement contingencies and thus provide an objective index of social learning.…”
Section: Discussionsupporting
confidence: 89%
“…These results could be considered contradictory to other studies (Hester et al, 2010), where punishment-driven learning has been found to improve learning performance; however, the nature of the tested tasks is different, i.e., procedural learning vs. associative learning, respectively. Besides, the recognized existence of differential pathways for reward- and punishment-driven learning reconciles both results.…”
Section: Introductioncontrasting
confidence: 95%
“…Interestingly, recent evidence shows that modifications in learned stimulusresponse mapping associations depend on error-related activity within medial pFCs when feedback is provided to participants (Hester et al, 2010). This finding indicates that processes related to monitoring and reweighting of a behaviorʼs value parallel those related to increases in executive control within prefrontal areas following errors; both mechanisms impacting how subsequent stimuli are handled.…”
Section: Discussionmentioning
confidence: 98%
“…Their results suggest a role for prefrontal areas, notably the right ventrolateral prefrontal area, in PES. Reinforcement learning studies have also pointed out associations between activity in prefrontal areas and associative learning (Brown & Braver, 2005;Nieuwenhuis, Holroyd, Mol, & Coles, 2004;Holroyd & Coles, 2002), and more specifically, this literature reported associations between errorrelated activity in pFCs and immediate changes in post-error behavior (Hester, Murphy, Brown, & Skilleter, 2010;Hester, Barre, Murphy, Silk, & Mattingley, 2008;Frank, Woroch, & Curran, 2005;Frank, Seeberger, & OʼReilly, 2004). However, the low temporal resolution of fMRI technique used in their study did not allow for disentangling the precise dynamics of brain mechanisms underlying post-error behavioral adjustments.…”
Section: Introductionmentioning
confidence: 93%